RESEARCH ON THE EXTERNAL TEMPERATURE DEPENDENCE OF THE TRDN-32000/110*KVA TRANSFORMER (E Conference Zone, 2024)
Power transformers are the most expensive and important components of any power system. The modern system is mainly focused on monitoring the start-up and overhaul of the transformer, which cannot fully guarantee the reliability of the work and the safety of their operation. By analyzing the influence of external factors on the temperature of power oil transformers in industrial enterprises and power networks, the reasons for the increase in the temperature of transformers and the expected problems are highlighted. As a result of the general analysis, measures to extend the working time of transformers were noted.